Dinner party animal : recipes to make every day a celebration - Cohen, Jake, 1993- (Harvest, an imprint of William Morrow, a division of HarperCollins, 2025)
" An impromptu cocktail party, casual brunch with friends, or celebratory dinner with family--food just tastes better when shared. For chef Jake Cohen, making a homemade meal from scratch for those you love is nothing short of magic. Now he's giving you everything you need to cook and entertain with ease in this highly anticipated collection of 100 delicious recipes and sixteen inventive menus for every mood, occasion, and possible guest list. With menus ranging from Treat Yourself Brunch to Veg Out, Meatballs to the Wall, Ride or Pie (a whole meal of pies!), That Was Tonight? (recipes that come together in a hurry), and even the ultimate Passover and Thanksgiving feasts, these are recipes you'll turn to again and again for special occasions and weeknight dinners alike. Each menu comes with a grocery list, prep and make-ahead guide, store-bought shortcuts, and a day-of run-of-show to take the stress out of hosting. Jake reminds us that we don't have to be perfect or even have a dining room table to entertain: anyone can do this, whether you're a comfortable home cook or a newbie in the kitchen. " --